Understanding interaction effect of arbuscular mycorrhizal fungi in rice under elevated carbon dioxide conditions. (15th October 2019) - Panneerselvam, Periyasamy; Sahoo, Sowarnalisha; Senapati, Ansuman; Kumar, Upendra; Mitra, Debasis; Parameswaran, Chidambaranathan; Anandan, Annamalai; Kumar, Anjani; Jahan, Afrin; Nayak, Amaresh Kumar
Abstract: Arbuscular mycorrhizal fungi (AMF), particularly the Glomerales group, play a paramount role in plant nutrient uptake, and abiotic and biotic stress management in rice, but recent evidence revealed that elevated CO2 concentration considerably reduces the Glomerales group in soil. In view of this, the present study was initiated to understand the interaction effect of native Glomerales species application in rice plants ( cv . Naveen) under elevated CO2 concentrations (400 ± 10, 550 ± 20, and 700 ± 20 ppm) in open‐top chambers. Three different modes of application of the AMF inoculum were evaluated, of which, combined application of AMF at the seedling production and transplanting stages showed increased AMF colonization, which significantly improved grain yield by 25.08% and also increased uptake of phosphorus by 18.2% and nitrogen by 49.5%, as observed at 700‐ppm CO2 concentration. Organic acids secretion in rice root increased in AMF‐inoculated plants exposed to 700‐ppm CO2 concentration. To understand the overall effect of CO2 elevation on AMF interaction with the rice plant, principal component and partial least square regression analysis were performed, which found both positive and negative responses under elevated CO2 concentration.